Nothing special - Herbach, Geoff (Herbach, Geoff. Felton Reinstein trilogy, 2012)
Continues the story of Wisconsin teenager and high school football player Felton Reinstein, how he relates to his friends Gus and Aleah and what he does when his little brother Andrew runs away on his way to orchestra camp.